Dar à educação física uma história nacional: a obra História da Educação Física e dos Desportos no Brasil, de Inezil Penna Marinho - Gyna de Ávila Fernandes (2020)
This thesis aims to understand how Inezil Penna Marinho's work História da Educação Física e dos Desportos no Brasil was conceived ‒ its manufacturing process ‒ and how the narrative proposed by this book informed and contoured the History of Brazilian Physical Education, becoming a work of reference. The book is organized in four volumes, under the subtitles Brazil-Cologne (Vol. I), Brazil-Empire (Vol. I) and Brazil-Republic (Vol. II, III and IV), and it was published by the Physical Education Division of the Ministry of Education and Health between 1952 and 1954. The research field of History of Printing presented itself useful for considering the History of Physical Education, since this area of knowledge seeks to identify the intentionalities involved in the production, elaboration, confection, distribution and reception of a printed paper, understanding the book as a cultural artifact, an object endowed with cultural, political, economic, social and educational interference. A group of authors have sought to understand the processes of production and reception of printed material. For this research, the studies of Roger Chartier, Robert Darnton and Don Francis Mckenzie were considered as tools of analysis to understand the manufacturing process of the work studied, while the Communications Circuit, proposed by Robert Darnton, guided the methodological path and the organization of this thesis’s narrative. Some factors are examined to identify how this work became a reference: the authorship, the publishing, the network of creation, the distribution and the targeted readers. As a result, it was found that the manufacturing process was influenced by different actors, whose actions, in a certain way, eventually converged in Inezil Penna Marinho’s figure. Thus, Marinho led the manufacturing process of the work, combining the different intentions of the other actors. And, as a network of creation, he manufactured this printed book, making it a reference work that tells the version of the National History of Physical Education, propagated and reverberated in the way of knowing, understanding and looking at the History of Physical Education.